Implementasi OLAP pada Data Kerja Praktik dan Tugas Akhir Menggunakan Framework Modular Cube JS - I Komang Arya Ganda Wiguna; Desak Putu Diah Kumala Dewi; I Gede Iwan Sudipa (Faculty of Computer Science, University of Jember, 2021)
The government's role in the implementation of higher education in Indonesia is to provide a university database. It is hoped that the government and the public can participate in assessing and conducting surveillance with the database. Every tertiary institution must report everything related to the implementation of education, starting from lecturer data, student data, and lecture data. In its performance, a Dikti Feeder application has been prepared that can transmit data. Each university will adjust the data entry following the Dikti standards. As one of the higher education providers, STMIK STIKOM Indonesia has been able to report data well, but specifically for final assignments and work practices, it has not been maximized due to the development of a separate system from the academic system. For this reason, a suitable system will be developed to accommodate Thesis and Internship data related to reporting on the Dikti Feeder by applying the Online Analytical Processing (OLAP) method using the Cube JS modular framework. Some of the tests carried out are schema file testing, frontend and backend testing, cube client testing, querying testing and load request testing showing the data can be displayed correctly and the process is successful.